ANALISIS KOMPARATIF KINERJA LINGKUNGAN ANTARA PERUSAHAAN HIGH PROFILE DAN LOW PROFILE PERIODE 2011 (STUDI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA) - MEGA RACHMAN, SEFTIAN Mega (Jurnal Akuntansi AKUNESA, 2013)
The purpose of this research is to explain CSR comparison report between highprofile and low profile companies listed on the Indonesia stock exchange in 2011.This research method is a descriptive one with 25 company objects. Assessment ofthe PROPER ranking of high profile companies are 9,26% gold, 37,04% green,50% blue,3,70%red, whereaslow profile ones are 29,63% green, 66,67% blue and3,70% black. The level of social disclosure of high profile industries is higherthan low profile. This looks in the high profile industries get37,04% GreenPROPER while low profile onesget 29,63%.Key words: CSR, high profile, low profile, PROPER.